2023
DOI: 10.1111/ggi.14544
|View full text |Cite
|
Sign up to set email alerts
|

A web‐based calculator combining Geriatric Nutritional Risk Index (GNRI) and Tilburg Frailty Indicator (TFI) predicts postoperative complications among young elderly patients with gastric cancer

Abstract: Nutritional status and frailty are significant indicators reflecting physiological reserve. We sought to establish and validate a web-based calculator containing the Geriatric Nutritional Risk Index (GNRI) and the Tilburg Frailty Indicator (TFI) together with general clinical information to predict total complications among elderly patients with gastric cancer.Methods: This was a prospective cohort study of 582 elderly patients with gastric cancer in a tertiary hospital in China. Nutritional status and frailty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, our findings also highlight the requirement for further studies that include comparisons between variable frailty measurements (e.g. G8 questionnaire [ 54 ], Frailty Index [ 55 ], Tilburg Frailty Indicator [ 56 ], which are widely used and validated in oncological patients or surgical patients [ 57 60 ]), and for the research to consider effect sizes, prediction accuracy, and pragmatic considerations like feasibility, importance and efficiency.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, our findings also highlight the requirement for further studies that include comparisons between variable frailty measurements (e.g. G8 questionnaire [ 54 ], Frailty Index [ 55 ], Tilburg Frailty Indicator [ 56 ], which are widely used and validated in oncological patients or surgical patients [ 57 60 ]), and for the research to consider effect sizes, prediction accuracy, and pragmatic considerations like feasibility, importance and efficiency.…”
Section: Discussionmentioning
confidence: 89%
“…Nutritional status has been demonstrated to be related to the prognosis of various cancers (20)(21)(22)(23). A study conducted by Sun et al (24) on the Prognostic Nutritional Index (PNI) in gastric cancer confirmed the association between poor nutritional status and poor survival outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…It is worth noting that studies have confirmed that mFI-11 can predict postoperative complications in patients undergoing spinal surgery, 38 , 39 but there is no relevant study on the relationship between frailty based on TFI and postoperative complications of spinal surgery. However, liu et al 40 have identified that frailty based on TFI emerged as a significant predictor of the post-operative quality of recovery and complications in patients with gynecologic cancer; Miao et al 41 have demonstrated the successful prediction of total complications among older adults with gastric cancer through the combined use of TFI with other factors, emphasizing the potential of TFI as a promising tool for frailty assessment and risk stratification in surgical populations. The trauma induced by lumbar surgery and anesthesia can incite diverse stress-related changes in the body.…”
Section: Discussionmentioning
confidence: 99%